Determinant of RAROC Moderated by COVID-19 (Asian Business Research, 2024)
This paper aims to explore determinants of RAROC moderated by Risk. This research used Model Panel Data to estimate variable relationship and yearly data for manufacturing Industry. The result is that The Ratio of Gross Profit margin is positively effect on RAROC. Debt to Equity Ratio has positively an effect on RAROC. Exchange Rate has positively an effect on RAROC. Interreaction DER dan COVID-19 has negatively an influence on RAROC. Interreaction Exchange Rate dan COVID-19 has negatively an influence on RAROC. COVID-19 is a pure moderating variable in this research for relationship between Exchange Rate and DER on RAROC.